2009
DOI: 10.2135/cropsci2008.08.0502
|View full text |Cite
|
Sign up to set email alerts
|

Flowering Phenology and Synchrony between Volunteer and Cropped Spring Wheat: Implications for Pollen‐Mediated Gene Flow

Abstract: Genetically engineered (GE) wheat (Triticum aestivum L.) volunteers could present a problem in cultivated wheat because they may facilitate movement of a GE trait to other volunteers or non‐GE wheat crops. However, volunteers can emerge periodically throughout the growing season and, thus, flowering overlap with the crop may be largely asynchronous, presenting a significant barrier to gene flow. Field experiments were initiated to determine the influence of volunteer wheat emerging at various densities and eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…However, the merits and limitations of pairedpollinator rows versus random, heterogeneous plant distributions remain unknown with regards to PMGF, and further investigation is certainly warranted. Paired-pollinator rows have, nevertheless, been utilized in several previous studies investigating flowering phenology and gene flow in wheat (Martin 1990;Hucl 1996;Willenborg et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, the merits and limitations of pairedpollinator rows versus random, heterogeneous plant distributions remain unknown with regards to PMGF, and further investigation is certainly warranted. Paired-pollinator rows have, nevertheless, been utilized in several previous studies investigating flowering phenology and gene flow in wheat (Martin 1990;Hucl 1996;Willenborg et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…1). The greatest flowering synchrony in all years and locations was obtained when volunteer emergence coincided with the crop, but there was always at least 1 day of flowering overlap between volunteer and cropped wheat populations when volunteers emerged within 150 GDD of the wheat crop (Willenborg et al 2009b). A total of 545,407 wheat seedlings were screened for hybridization among both locations and years.…”
Section: Resultsmentioning
confidence: 99%
“…However, spring wheat phyllochron (time between elongation of successive leaves) intervals range between 80 and 100 GDD (Bauer et al 1984;Shirtliffe et al 2000) and therefore, we can expect wheat plants possessing one more or one less leaf to have emerged (and probably flower) within the hybridization window (Willenborg et al 2009b). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because wheat can flower in as few as 3–5 d (Hucl, 1996) and volunteer wheat plants will emerge and flower within wheat crops, flowering asynchrony with volunteer populations may be an important barrier to gene dispersal between cropped and volunteer wheat populations. Willenborg et al (2009) showed that volunteer wheat emerging after a spring wheat crop exhibited considerable flowering synchrony with the crop. However, volunteer plants emerging after a spring wheat crop cannot be selectively removed from the crop, and thus present a challenge with regard to minimizing PMGF.…”
mentioning
confidence: 99%